Vicissitudes do intelectual público: um estudo de caso sobre Mário Pedrosa (1944-1968) - Josnei Di Carlo (Ciências Sociais Unisinos)
After returning from exile in 1945, Mario Pedrosa (1900-1981) became a specialist in modern art. Concomitantly with his professionalization as an art critic, he became a public intellectual, because of political intervention in the disputes through the big press. With this, his political ideas circulated to a broad audience, unaccustomed to the subtleties of the arts. Unlike their cultural columns, the policies columns were seasonal, dictated by the moments of social effervescence. Gathering yours columns between 1945 and 1968, we note the seasonality of its political intervention. However, there were conditions for this to occur.